Analisis Indeks Keluarga Sehat untuk Mendukung Program Promosi Kesehatan - Reni Murnita; Asih Prasetyowati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
Health development starts from the smallest unit of society, namely the family. The Ministry of Health establishes an operational strategy for health development through the Healthy Indonesia Program with a Family Approach (PIS-PK). Data collection activities carried out in the PIS-PK aim to obtain health data for each family member by the Puskesmas. This study aims to determine the description of the index of healthy families in the working area of Puskesmas Batang I by using 12 indicators of healthy families related to the Health Promotion Program. This research is a quantitative study carried out in a descriptive observative manner, namely by analyzing the data narrative. Desa Kecapak has an index value of 0.08 (Unhealthy Family), Kelurahan Sambong has an index of 0.2 (Unhealthy Family), Kelurahan Proyonanggan Utara has an index 0.13 (Unhealthy Family), and Kelurahan Proyonanggan Tengah has an index 0 , 21 (Unhealthy Family). Puskesmas Batang I work area has an index of 0.18 and is in the Unhealthy Family category. The families that were recorded had not had total coverage, which was still 54.2%. The health promotion program of the Batang I Puskesmas includes data collection on Clean dan Healthy Behavior/Perilaku Hidup Bersih dan Sehat (PHBS), training for posyandu cadres, self-awareness surveys/Survey Mawas Diri (SMD), and guidance for Alert Village/Desa Siaga.. The Health Promotion Program can refer to data on the healthy family index and PHBS by looking at the low indicator coverage of healthy families. Puskesmas can cooperate with educational institutions so that the number of families being recorded is maximized. Based on the healthy family index coverage figures, the health promotion program must synergize with the Disease Eradication Program, especially pulmonary TB disease, hypertension, and mental disorders. It is hoped that the development of posyandu and posbindu cadres can increase the coverage of the healthy family index, especially in increasing family knowledge about infectious and non-communicable diseases